2020
DOI: 10.3389/fvets.2020.569098
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cyclovirus Identified in Broiler Chickens With Transmissible Viral Proventriculitis in China

Abstract: In October 2018, an outbreak of transmissible viral proventriculitis (TVP) occurred in 30-day-old commercial broiler chickens on a farm in Weifang, China. TVP, an infectious viral disease characterized by runting and stunting, is associated with many viruses, and has a significant economic impact on the global poultry industry. TVP is diagnosed according to clinical symptoms, gross and histological lesions, and negative PCR results for pathogenic bacteria, avian leukosis virus subgroup J, Marek's disease virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Cycloviruses in chickens were found to be associated with transmissible viral proventriculitis (TVP) that resulted in lesions, runting, and stunting [58]. Lima et al [59] identified cycloviruses in malabsorption syndrome from chickens in Brazil.…”
Section: Circovirusesmentioning
confidence: 99%
“…Cycloviruses in chickens were found to be associated with transmissible viral proventriculitis (TVP) that resulted in lesions, runting, and stunting [58]. Lima et al [59] identified cycloviruses in malabsorption syndrome from chickens in Brazil.…”
Section: Circovirusesmentioning
confidence: 99%
“…Since then, CPNV was reported in the USA, Spain, France, UK, Poland and Brazil [ 8 13 ]. Studies on TVP etiopathology also imply the other viruses involvement, including infectious bursal disease viruses (IBDV) of the Birnaviridae family, infectious bronchitis viruses (IB) of the Coronaviridae family, reoviruses (REO), picornaviruses, fowl adenoviruses (FAdV), adeno-like viruses, Gyrovirus homsa1 (GyH1, also known as Gyrovirus 3, GyV3), Cyclovirus (CyCV) of the Anelloviridae [ 14 , 15 ] and chicken Circovirus (CCV) of the Circoviridae [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on genome-wide pairwise nt sequence identities and a phylogenetic analysis, at least 52 cyclovirus species have been formally recognized by the International Committee on Taxonomy of Viruses (ICTV) (https://talk.ictvonline.org/ictv-reports/ictv_online_ report/ssdna-viruses/w/circoviridae/660/genus-cyclovirus, accessed on 18 September 2021). Cycloviruses have been detected in various mammals, birds and arthropods [1][2][3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Furthermore, an endogenous cyclovirus element was identified from a rodent-infecting nematode, suggesting that cycloviruses might infect non-arthropod parasitic invertebrates [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an endogenous cyclovirus element was identified from a rodent-infecting nematode, suggesting that cycloviruses might infect non-arthropod parasitic invertebrates [12]. Since the discovery of cycloviruses was solely based on the identification of viral DNA (by degenerate PCR and metagenomic sequencing) [1][2][3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20][21], the definitive hosts and pathogenesis of cycloviruses are largely unknown [1,2,4,5,12,13]. However, cycloviruses have been reported in humans with diarrhea [21], encephalitis [21], paralysis [14] and pneumonia [10].…”
Section: Introductionmentioning
confidence: 99%